The Role of Subsidies in Promoting Italian Joint Ventures in Least Developed and Transition Economics - Enrico Santarelli; Giorgio Barba Navaretti; Marco Vivarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
This paper analyses the impact of subsidies to promote Italian joint ventures (JVs) with firms in LDC and transition economies. The empirical analysis is carried out on a unique dataset of 172 JVs interviewed during 1998 by means of a closed-answer qualitative-quantitative questionnaire. The main finding of the study is that although there is a significant deadweight component in incentive policy, subsidised firms are significantly more likely to grow. Moreover, JVs comprising new firms (which need to grow to survive) also achieve a higherthan- average employment performance, and so too do (labour intensive) JVs motivated by the search for lower labour costs, and JVs in East European countries.
Keywords: 330